Long-term site fidelity of killer whales to a herring spawning ground using photo-identification - Ástrós Eva Ársælsdóttir 1997- (2022)
Marine species are unhindered with regards to movement in the ocean and some species are known to voyage over long distances in search for food, mates, breeding grounds, etc. Understanding the distribution and movements of apex predators, such as killer whales, is essential to learn more about their impacts on species in lower trophic levels as well as allowing scientists to gain more information on their population ecology, population structure and genealogy. In this study, photo-identification data was used to investigate whether killer whales exhibited long-term site-fidelity to a herring spawning ground off Iceland. Data collected in the summer of 2001 was analyzed and compared to data from 2008-2020. Of 69 identified killer whales identified in 2001, 37.7% were re-sighted in the time period 2008-2020. Lagged identification rates indicated that this population followed a closed population model, even though some emigration and re-immigration occurred. Transition probabilities show high site-fidelity within time periods as well as a low probability of individuals being re-sighted between time periods. Identifying factors that drive differences in movements is relevant for us to monitor population changes and changes in movement patterns, which may indicate changes in lower tropic levels.